Isolation of Cellulose Degradation Bacteria (CDB) from acid soil as a potential candidate of organic waste degradation - Eri Samah (JERAMI : Indonesian Journal of Crop Science, 2019)
Background: The study aimed to obtain CDB with high degraded activities, determined growth curve, protein content, and cellulase maximum activity (exoglucanase and endoglucanase). Method: The cellulose activity calculated according to Miller (1959), protein content was measured by Bradford method with bovine serum albumin (BSA) as a standardize protein. Result: Six isolates of CDB were found as potential degradation of organic waste (Km25, Sr75, Jm, U6, G8, and Km13). Growth curve, protein level, and protein maximum activity occurred on day-3. The largest diameter of clear zone of six isolates was Km25, Sr75, Jm, U6, G8, and Km13 (3.32, 3.31, 2.41, 2.36, 2.19, and 2.04 mm, respectively). Endoglucanase and exoglucanase maximum activity were 0.011-0.402 IU/mL and 0.0028-0.155 IU/mL, respectively. Conclusion: Six isolates showed high activities of cellulase with diameter of clear zone ? 2 cm (Km25, Sr75, Jm, U6, G8, and Km13). Growth maximum curve was on day-3. Highest endo- and exoglucanase activities were on day-3 (0.402 IU/mL and 0.155 IU/mL, respectively) in Jm isolate. Keywords: Identification, degradation, clear zones, cellulase.